Analisis Program Intervensi Gizi Spesifik Pada Ibu Menyusui Terhadap Kejadian Stunting Pada Anak Usia 25-36 Bulan Di Wilayah Kerja Puskesmas Antang Kota Makassar - Nabilah Zainal; Arman A; Sitti Patimah (PT.Mantaya Idea Batara, 2021)
The critical period for a child's growth and development called the First 1000 Days of Life is influenced by the nutritional status of the mother during breastfeeding. The nutritional problem that can occur at this time is stunting (short). One of the programs contained in the First 1000 Days of Life Movement in an effort to prevent stunting is specific nutrition intervention. The aim of this research conducted is to knowthe analysis of the specific nutrition intervention program for breastfeeding mothers onthe occurrence of stunting through infectious diseases in children 25-36 months in the work area of the Antang Community Health Center, Makassar in 2021. This research used quantitative research by using path analysis method. The populationsof this research were all children in age 25-36 months with 543 children. The samples of this research were 128 children, with the mother of the children as the respondent. The sampling technique in this study was purposive sampling. The results of this study indicate that the significance value of (1) the effect of breastfeeding counseling on the occurrence of stunting is 0.006, (2) the IMD on the incidence of stunting is 0.162, (3) exclusive breastfeeding on the incidence of stunting is 0.933, (4) the frequency of breastfeeding on the occurrence of stunting is 0.617, (5) the time giving complementary feeding to the occurrence of stunting is 0.446, (6) the effect of breastfeeding counseling on the occurrence of stunting through infectious diseases is the direct influence value 0.245, while the indirect effect value is 0.00015, (7) the effect of IMD on the occurrence of stunting through infectious diseases is the direct influence value of 0.126, while the indirect effect value is 0.00405, (8) the effect of exclusive breastfeeding on the occurrence of stunting through infectious diseases with the direct effect value is 0.010, while the indirect effect value is 0.0233, (9 ) the effect of breastfeeding on the occurrence of stunting through the direct effect is 0.045, while the value of the indirect effect is 0.0604, (10) the effect of the time giving complementary feeding to the incidence of stunting through infectious diseases with the direct effect value is 0.097 while the indirect effect is 0.01115. The conclusion of this research indicate that specific nutrition intervention program for breastfeeding mothers on stunting has not shown a reduction in stunting occurrence in the work area of the Antang Community Health Center, Makassar City. Suggestions, it is hoped that health services need to provide socialization and counseling to mothers about the importance of breastfeeding counseling, exclusive breastfeeding, early initiation of breastfeeding, the right time for giving complementary feeding for mothers.